PROSPEK USAHA PEMBUATAN PAKAN IKAN DENGAN TAMBAHAN Azolla microphylla DI DESA TEGAL REJO KECAMATAN BELITANG KABUPATEN OKU TIMUR - Munsiarum (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The objectives of this research are: (1) To know the production of fish feed (pellet) with additional Azolla microphylla in Tegal Rejo Village Belitang Sub-District, OKU Timur Regency, (2) Analyze the income on fish pellet production business with additional Azolla microphylla in Desa Tegal Rejo Belitang Sub-District, OKU Timur Regency, (3) Analyzing the development of fish meal business (pellet) with additional Azolla microphylla in Tegal Rejo Village Belitang Sub-District, OKU Timur Regency. This research was conducted in Tegal Rejo Village of OKU Timur Regency. The research has been conducted in Febuary 2015 until it is completed by purposive or purposive method, considering that in Tegal Rejo Village, OKU Timur Regency is one of the villages where there is a business of home fish production and the area has technical, economical and Ecological in the implementation of fish production business (home industry) and enough in the research criteria. This study found that in 2014 the business actors produce 9,790 kg / year with the price of Rp 5000 / kg by giving revenue of Rp 48,950,000 with production cost Rp 7,425,000, thus giving income amounting to Rp -23,475,000. In 2015 the business of making fish feed produces 7,150 kg / year with the selling price of Rp 6,500 / kg. Receipts obtained by business actors amounted to Rp 46,475,000, with the use of production costs of Rp 26,193,250, thus earning revenue of Rp 20,281,750. In 2016 the business of making fish feed with additional azollamicrophylla producing 7,920kg / year with the selling price of Rp 7.000 / kg then the revenue is Rp 55.440.000, the use of production cost of Rp 30.324.000 then the income is Rp 25.116.000 and the making business Fish feed with additional Azolla microphylla in Tegal Rejo Village Belitang District, OKU Timur Regency is feasible to be developed. By fulfilling the criteria of NPV value Rp 16.867.875, IRR value of 31.86%., And the value of Net B / C obtained 1.5.